Dejavniki rodnostnega obnašanja v Sloveniji - Josipović, Damir (Geografija Slovenije, 2004)
The present research considers factors of fertility behaviour in Slovenia. The analysis of the whole territory of Slovenia is complemented with the empirical research including a fieldwork in three sample regions, all of it being rounded off with the synthesis in a form of conclusions and mutual comparisons. Sample regions (Prekmurje, Zasavje in območje upravne enote Domžale) represent three main types of regional-geographic structure. The research temporally coincides with the period of second demographic transition in Slovenia commencing after 1980. The emphasis was put on recent development of fertility in Slovenia and sample regions. That was also a starting point of most comparisons evaluating the role of various factors in shaping fertility behaviour as well as possibilities of geographical approach to fertility research. In this sense the influence of geographical factors of fertility was of particular interest.